Survey for assessing the status of incidence of virus diseases in tissue culture and sucker propagated banana gardens - S, Basavaraj; K T, Rangaswamy; M, Bhagyashree (Indian Journal of Plant Protection, 2020)
anana (Musa paradisiaca) is a herbaceous plant belonging to the family Musaceae of the genus Musa and is native to the tropical region of South East Asia. Banana is cultivated throughout tropics and subtropics. The banana viral diseases have been causing considerable damage to banana production in banana growing areas due to their systemic invasion and common spread through vegetatively propagated planting materials. Banana gardens established using tissue culture derived plants as well as suckers were surveyed to assess the status of banana viruses. Random samples were collected in individual field showing characteristic viral symptoms and confirmed for the infection of respective viruses through PCR or ELISA. Results revealed occurrence of all four major viruses viz., BBTV, BSV, CMV and BBrMV. Among the four viruses, the most frequent were BBTV and BSV. The incidence in ratoon crop (2.8%) was significantly high compared to main crop (1.6%) irrespective of type of planting material used for establishing plantations.